On the Development of a Web-Based M-Learning System for Dual Screen Handheld Game Consoles - Al-Khalifa, Hend S. (International Journal of Interactive Mobile Technologies (iJIM), 2011)
This paper presents our experience on the design and development of an M-Learning web-based system for the Nintendo DSi game console. The paper starts by addressing the difficulties that emerged from the lack of resources on design guidelines for dual screen devices also the absence of adequate techniques and methods to support the design decisions. Then it explains how we overcame these challenges by adopting a design decision suitable for the screen requirements of the Nintendo DSi console. Finally, we present the components of our M-Learning system and the results of a preliminary usability evaluation.